2005
DOI: 10.1097/01.ijg.0000145811.62095.fa
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Management of Elevated Intraocular Pressure After Silicone Oil Injection

Abstract: Chronic intraocular pressure elevation occurs in a minority (11%) of patients who are treated with silicone oil. Most of these eyes are effectively treated with antiglaucoma medications. Eyes that do not respond to medical therapy may be effectively managed with glaucoma drainage implant placement in an inferior quadrant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
87
1
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(94 citation statements)
references
References 34 publications
3
87
1
3
Order By: Relevance
“…One patient was uncontrolled with topical therapy and required surgical intervention. This rate is consistent with previously reported rates utilizing silicone oil 15,16…”
Section: Discussionsupporting
confidence: 93%
“…One patient was uncontrolled with topical therapy and required surgical intervention. This rate is consistent with previously reported rates utilizing silicone oil 15,16…”
Section: Discussionsupporting
confidence: 93%
“…The true incidence of glaucoma after silicone oil injection is difficult to ascertain. The rates of elevated IOP or glaucoma range from 2.2% at 6 months to 56% at 8 months [5675], with more recent studies reporting lower rates, likely as a result of improvements in surgical techniques and materials. Higher viscosity silicone oil (5000 centistokes) has been noted to result in fewer emulsified silicone droplets in the anterior chamber and a lower risk of glaucoma [76].…”
Section: Glaucoma After Silicone Oil Injectionmentioning
confidence: 99%
“…Aqueous suppressants are used to reduce IOP. In a study by Al-Jazzaf et al [75], 78% of patients (40 of 51) with glaucoma after PPV and silicone oil injection were treated successfully with medications alone. The IOP was controlled in most eyes with topical beta-blockers and prostaglandin analogues.…”
Section: Glaucoma After Silicone Oil Injectionmentioning
confidence: 99%
“…Long-term glaucoma following SSO use is uncommon in current surgery, but past studies have indicated an incidence ranging from 3% to 40% of cases 4,10,14,15. Some of these cases can develop secondary glaucoma 5,1416.…”
Section: Introductionmentioning
confidence: 99%